Analysis of transfer of tumor-inducing plasmids from Agrobacterium tumefaciens to Petunia protoplasts. - Virts, E L (1985)
Petunia protoplasts were infected with the virulent Agrobacterium tumefaciens strain A348 or the avirulent strain A136 (lacking a Ti plasmid). The infection process was stopped at various time intervals up to 24 h after inoculation, and the DNA from the plant cells was isolated. Southern blot analysis indicated that the DNA isolated from infected Petunia cells was not detectably contaminated by bacterial DNA from lysed Agrobacterium cells. Analysis of the DNA from the virulent infections suggested that the transferred DNA (T-DNA) may be transferred to the plant cell rapidly (within 2 to 6 h) after the bacteria bind to the cell wall and that the T-DNA may exist in a rearranged state which is stable over the time period investigated. Dot blot analysis indicated that regions far outside the T-DNA may be transferred to the plant cell. Most of the DNA transferred to the plant cell during the initial hours of infection is rapidly degraded.